TREE-RING RECORDS FROM CENTRAL FENNOSCANDIA: THE RELATIONSHIP BETWEEN TREE GROWTH AND CLIMATE ALONG A WEST-EAST TRANSECT - Linderholm H.W.; Solberg B.O.; Lindholm M. (My University, 2003)
Nine Scots pine tree-ring-width chronologies were compared regarding growth variability and response to climate along a gradient of oceanicity–continentality at 62–64°N in central Fennoscandia. The study revealed higher growth variance and stronger response to climate in the oceanic area west of the Scandi navian Mountains, compared to the more continental areas further east. However, there was a gradual change in radial tree growth and response to climate along the gradient, where tree growth in a transition zone between oceanic and continental climate showed positive correlations with radial tree growth in both oceanic and conti nental areas. Pine growth responded positively to summer temperatures in the western areas, and positively to summer precipitation in the east. Generally, pine growth showed a weaker relationship with the North Atlantic Oscillation (NAO) than with temperature and precipitation. During the summer, pine responded to the NAO only in western Fennoscandia, while during the winter pine responded to the NAO in both western and eastern Fennoscandia. This suggests that, during winter, the NAO is an adequate measure for climatic variations important for pine radial growth along the whole studied gradient, while, in the summer, the NAO is an inadequate measure for climatic variations important for pine radial growth east of the Scandinavian Mountains. During the second half of the twentieth century, pine growth in western Fennoscandia displayed reduced sensitivity to climate, while the opposite was found in the east. Indications of growth stress were found in one site east of the Scandinavian Mountains, and, as increasing temperatures have been accompanied by increasing precipitation in Fennoscandia throughout the twentieth century, we suggest that a change in climate regime from subcontinental to suboceanic caused those trees to experience climatic stress. However, trees in either oceanic or more continental areas did not seem to respond negatively to recent climatic change.
Keywords: Tree rings; dendrochronology; dendroclimatology; Pinus sylvestris; Scots pine; North Atlantic Oscillation; NAO; climatic change; Fennoscandia